Evaluation of coronavirus diseases (COVID-19) in terms of epidemiological and clinical features, comorbidities, diagnostic methods, treatment, and mortality - Nedim Cekmen; Zeynep Ersoy; Yağılz İlteriş Günay; Amir Aslan Ghavam; Muhammed Yavuz Selim Tufan; İbrahim Mete Şahin (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) causes COVID-19. On March 11, 2020, the WHO declared it a pandemic. SARS-CoV-2 indicates that it poses a significant threat to public health and global economy. The aim of the study was to determine (a) patient characteristics, (b) demographic characteristics, (c) comorbidities, diagnostic methods used, treatment, and outcomes, and (d) mortality rates of patients. MATERIALS AND METHODS: This retrospective cohort study included 352 hospitalized adult patients from Baskent University Hospital in Ankara who were confirmed cases of COVID-19 between March 2020 and March 2021. SPSS v. 14.0 was used for statistical analysis. RESULTS: Out of 352 patients, 55 died (males: 37, females: 18), while 297 survived (males: 162, females: 135). The most common comorbidities were hypertension (HT), diabetes mellitus (DM), coronary artery disease (CAD), cancer, Vitamin D deficiency, and chronic obstructive pulmonary disease. Comorbidities associated with mortality rate were obesity (33%) (P = 0.118), Vitamin D deficiency (28%) (P = 0.009), DM (25%) (P = 0.004), CAD (21.2%) (P = 0.142), cancer (20.9%) (P = 0.084), and HT (16.6%) (P = 0.90). Normal ward admission resulted in death in 67.3% and survival in 93.9% (P = 0.001), intensive care unit (ICU) admission resulted in death in 69.1% and survival in 18.5% (P = 0.001), and oxygen therapy was used in 80% death and survival in 39.4% (P = 0.001). CONCLUSIONS: Our study shows that male gender, advanced age, and presence of comorbidities in COVID 19 patients are at higher risk for severe disease, ICU admission, and death. We emphasize that morbidity and mortality can be reduced by early and comprehensive identification of risk factors and the warning systems that will meet the ICU needs of these patients.